Rediseño de la distribución de planta aplicado a Isoplasticos S.A.S. (2018)
The purpose of this research is to solve an engineering problem by designing an adjustable solution for other similar conditions. The chosen situation was the layout redistribution of an injection and blow molding company, called ISOPLASTICOS S.A.S. which is currently in an accelerated growth addressed by its main client. In order to solve this problem, a solution methodology was designed based on the theories of the SLP, Systematic Layout Planning. The methodology DMAIC was used as the way to approach the problem.